Apical transportation associated with ProTaper® Universal F1, F2 and F3 instruments in curved canals prepared by undergraduate students - Manoel BRITO-JÚNIOR; André Luis FARIA-; Carla Cristina CAMILO; Rodrigo Dantas PEREIRA; Neilor Mateus Antunes BRAGA; Manoel Damião SOUSA-NETO (University of São Paulo, 2014)
Objective: This study evaluated apical transportation associated with ProTaper® Universal Fl, F2 and F3 rotary files in curved canais prepared by undergraduate students. Material and Methods: Twenty mesial roots of mandibular molars with curvatures ranging between 25° and 35° were selected. Mesiobuccal canals were instrumented by twenty students with the ProTaper® system (Dentsply-Maillefer, Ballaigues, Switzerland) according to the manufacturer's instructions. Pre-fiaring was performed with Sl and SX files. A #15 K-file was inserted into the root canal up to the working length (WL), and an initial digital radiograph was taken in a buccolingual direction (baseline). Afterwards, the S1, S2, F1, F2, and F3 files were employed up to the WL. Other radiographies were taken in the same orientation of the baseline after the use of the Fl, F2, and F3 files, with each file inserted into the root canal. The radiographic images were overlapped, and the Image J software was used to measure the distance between the rotary files' ends and the #15 K-file's end, characterizing the apical transportation. Data were analyzed by Repeated Measure ANOVA and by the SNK post hoc test (P<0.05). Results: It was verified that file size affected apical transportation significantly (P<0.001). The F3 file showed higher apical transportation than Fl and F2, while between these last files there was no difference. Conclusion: The undergraduate students produced lower apical transportation in curved canals when they did not use the F3 rotary file.